2005
DOI: 10.1001/archneur.62.8.1217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Discontinuing Aspirin Therapy on the Risk of Brain Ischemic Stroke

Abstract: Background: Aspirin, or acetylsalicylic acid, is widely used to prevent ischemic vascular disease. Clinical and experimental data suggest that a rebound effect occurs 4 or fewer weeks after interruption of aspirin therapy. Objective: To study the discontinuation of aspirin therapy as a risk factor for ischemic stroke (IS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(146 citation statements)
references
References 20 publications
4
141
0
1
Order By: Relevance
“…Acute cardiac events are noted within 10 days of ASA withdrawal and are due to coronary thrombosis. There are also clinical and experimental data that the "rebound thrombosis phenomenon" increases cerebrovascular event rates as well (13). These findings support the recommendation to restart ASA treatment within 8-10 days after a major procedure for which ASA withdrawal was deemed necessary.…”
Section: Commentssupporting
confidence: 64%
“…Acute cardiac events are noted within 10 days of ASA withdrawal and are due to coronary thrombosis. There are also clinical and experimental data that the "rebound thrombosis phenomenon" increases cerebrovascular event rates as well (13). These findings support the recommendation to restart ASA treatment within 8-10 days after a major procedure for which ASA withdrawal was deemed necessary.…”
Section: Commentssupporting
confidence: 64%
“…106 107 Caution is required if aspirin therapy is interrupted when prescribed for secondary prophylaxis due to the high risk of thrombotic events. [34][35][36] The association of thienopyridene or aspirin use with the risk of post-ESD bleeding has been examined in several studies of gastric ESD. These studies are, however, retrospective single-centre case studies with a variety of APAs, and differences in regimens for discontinuing or continuing therapy.…”
Section: Polypectomy On Antithrombotic Therapymentioning
confidence: 99%
“…Our findings did not greatly differ from the previous studies; AMI occurred in 1 patient (4.3%) in the discontinuation group. With respect to the period from the withdrawal of antithrombotic agents to the occurrence of thromboembolic events, one study reported that about 70% of post-withdrawal cerebral infarctions occurred within 10 days after withdrawal (5), and the PRoFESS study sub-analysis found that there was a significantly higher stroke recurrence rate within 1 week after the withdrawal of antiplatelet agents (6). In the present study, the patient in the discontinuation group who suffered AMI had discontinued all antithrombotic agents (aspirin and ticlopidine) 1 week earlier and was receiving heparin bridging therapy, but suffered AMI on the day of the procedure (7th day of withdrawal), a similar result to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the antithrombotic agent is continued, perioperative thrombosis and embolism can be prevented, but the risk of bleeding increases. It has been reported that the cessation of warfarin results in serious thromboembolism in 1% of patients and death in 80% of this 1%; the cessation of aspirin leads to a 3.4-fold increase in the odds ratio for cerebral infarc-tion (4,5). A sub-analysis in the Prevention Regimen for Effectively Avoiding Second Strokes (PRoFESS) study of secondary stroke prevention also found that cessation of antiplatelet agents resulted in approximately a 5-fold increase in the incidence of stroke recurrence within one week (6).…”
Section: Introductionmentioning
confidence: 99%